Thermal Annealing of Neutron Irradiated Ammonium and Potassium Dichromate - Abdul Khalik, Karim; Al-Abbasi, M.; Numan, A. (Iraqi Journal of Science, 2025)
A modified solvent extraction study was made to assess the validity of previously published claim that, în neutron irradiated ammonium dichromate heating leads to the generation of a reducing species that cause lowering of the value of retention. Simultaneous investigation of the behavior of both the ammonium and potassium salts showed this claim to be incorrect.